Mobilidade cicloviária em viagens a campi universitários - estudo de caso - Grau, Roberta Iza (Universidade Federal de São Carlos, 2015)
Nowadays, universitary campi are suffering from negative reflexes brought by the high motor vehicles’s rate. This rate have been troubling users’ daily commutings and could be lessened if active modes of transportation, walking and cycling, were adopted. The aim of this research was the comprehension of behaviour change capacity of an academic comunity to adopt the bicycle as a mode of transportation for commuting to São Carlos’ Federal University, São Carlos, Brasil. In this work, a survey was conducted, via internet and one-on-one interviewing, with 473 participants. The survey was adapted from Smith et al. (2004) and based on Prochaska and DiClemente (1982, 1983) Transtheoretical Model of Behaviour Change, MTMC. The participants were professors, technical-administrative employees, graduate and post-graduate students. The sample’s profile was of a graduate and post-graduate student, aging 18 to 35 years-old, residing up to 5 km away from the campus and using motor vehicles to commute. MTMC’s results showed the bicycle’s major motivator and barrier to be the schedule freedom and the lack of cycling infrastructure, respectively.
Keywords: Modelo transteórico de mudança comportamental; Mobilidade urbana; Campus universitário; Bicicleta; Ciclismo; Transtheoretical model of behavior change; Urban mobility; Campus university; Bicycle; Cycling; ENGENHARIAS::ENGENHARIA CIVIL